2022
DOI: 10.1111/ene.15407
|View full text |Cite
|
Sign up to set email alerts
|

Free vitamin D3 index and vitamin D‐binding protein in multiple sclerosis: A presymptomatic case–control study

Abstract: Background and purpose High levels of 25‐hydroxyvitamin D3 (25[OH]D3) are associated with a lower risk for multiple sclerosis (MS). The bioavailability of 25(OH)D3 is regulated by its main plasma carrier, vitamin D‐binding protein (DBP). Free 25(OH)D3 can be estimated by also measuring DBP concentration. In addition, DBP has immunomodulatory functions that may independently affect MS pathogenesis. No previous studies have assessed free 25(OH)D3 or DBP in presymptomatically collected samples. This study was und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
(106 reference statements)
2
3
0
1
Order By: Relevance
“…In the current study, the plasma level of DBP was significantly lower in patients than in the healthy controls and lowest in the RRMS-relapse group. This is consistent with previous observations [12][13][14]. Some other studies reported no change in circulating DBP in relapsing MS during remission and relapse [16] and during remission [12] as compared to healthy controls, while at least one study [18] reported higher DBP levels in RRMS.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the current study, the plasma level of DBP was significantly lower in patients than in the healthy controls and lowest in the RRMS-relapse group. This is consistent with previous observations [12][13][14]. Some other studies reported no change in circulating DBP in relapsing MS during remission and relapse [16] and during remission [12] as compared to healthy controls, while at least one study [18] reported higher DBP levels in RRMS.…”
Section: Discussionsupporting
confidence: 92%
“…The association of changing levels of DBP with the presence of MS is, however, controversial. Various studies have suggested that DBP levels are (i) low in MS patients' cerebrospinal fluid (CSF), especially in those patients with relapsing MS [10,11]; (ii) low in the serum of patients with MS compared to the serum of healthy controls [12], and the lowest in relapsing-remitting (RRMS) patients [13,14]; (iii) higher in the CSF of patients with secondary progressive MS (SPMS) [15]; (iv) not different in the serum levels in patients with stable or active disease compared to the serum levels of controls [16,17]; and (v) according to at least one study [18], higher in RRMS patients. The implications of low DBP's association with low circulating free vitamin D are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence for an immunomodulatory role of vitamin D in multiple sclerosis [ 35 ]. Other studies have demonstrated some utility of vitamin D binding protein in distinguishing people with multiple sclerosis versus controls [ 36 , 37 ], or risk of developing multiple sclerosis [ 38 ]. Vitamin D binding protein has been shown to be expressed on spinal cord neurons, pia mater and grey matter within the brains of people with multiple sclerosis, and in an animal model of multiple sclerosis, high vitamin D binding protein appeared to mitigate beneficial effects of vitamin D3 supplementation and inhibit recovery [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Başka bir araştırmada ise 20 yaşından küçük bireylerde yüksek serbest D3 vitamin indeksi daha düşük MS riski ile ilişkilendirilirken 30-39 yaş aralığında yüksek VDBP seviyeleri daha düşük MS riski ile ilişkilendirilmiştir. Bu durum MS etiyolojisinde VDBP'nin rolünün de önem arz ettiğini ortaya koymaktadır (18). D vitamini aktif forma dönüştükten sonra biyolojik fonksiyonlarını yerine getirebilmesi için, T hücreleri, dendritik hücreler, monositler, makrofajlar, ve aktif B hücreleri dahil olmak üzere hemen hemen tüm bağışıklık hücrelerinin çekirdeğinde bulunan D vitamini reseptörüne (VDR) bağlanması gerekir (12).…”
Section: Introductionunclassified